2021
DOI: 10.1002/jdn.10086
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid protects cerebral cortex, hippocampus, and striatum against oxidative damage and cholinergic dysfunction in an experimental model of manic‐like behavior: Comparison with lithium effects

Abstract: Bipolar disorder is characterized by episodes of depression and mania, and oxidative stress has been associated with the observed neurochemical changes in this disease. We evaluated the effects of gallic acid on hyperlocomotion, acetylcholinesterase activity, and oxidative stress in an animal model of ketamine‐induced mania. Rats were pretreated orally with vehicle, gallic acid (50 or 100 mg/kg), or lithium (45 mg/kg twice a day) for 14 days. Between days 8 and 14, the animals also received ketamine (25 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Gallic acid (GA) a phenolic acid that is widely spread in the plant kingdom was used in the treatment of ketamine-induced mania in rats and compared to the action of lithium. Similarly to lithium (45 mg/g twice a day) GA (50 and 100 mg/kg) administered for 14 days decreased the hyperlocomotion of the animals, induced the antioxidant properties and prevented the cholinergic disfunctions in the brain (Recart et al, 2021). In the studies of collaborators (2016, 2017) quercetine administered intraperitoneally (10-40 mg/kg b. w.) showed antioxidant properties and inhibition of protein kinase C. In turn the flavonoid regulated sleep deprivation and diminished the…”
Section: Treatment Of Bipolar Disorder and Bioactive Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…Gallic acid (GA) a phenolic acid that is widely spread in the plant kingdom was used in the treatment of ketamine-induced mania in rats and compared to the action of lithium. Similarly to lithium (45 mg/g twice a day) GA (50 and 100 mg/kg) administered for 14 days decreased the hyperlocomotion of the animals, induced the antioxidant properties and prevented the cholinergic disfunctions in the brain (Recart et al, 2021). In the studies of collaborators (2016, 2017) quercetine administered intraperitoneally (10-40 mg/kg b. w.) showed antioxidant properties and inhibition of protein kinase C. In turn the flavonoid regulated sleep deprivation and diminished the…”
Section: Treatment Of Bipolar Disorder and Bioactive Compoundsmentioning
confidence: 96%
“…That is why several experimental studies focus on the development of drug candidates that could restore Frontiers in Pharmacology frontiersin.org oxidation-reduction balance. In the light of this information, natural products that are proved to exhibit antioxidant properties are important to drug candidates in the reduction of manic episodes (Recart et al, 2021). Herbal intervention in bipolar disorder is recommended and prescribed, accompanied by mood stabilizers (Currier and Trenton, 2002;Mohr et al, 2005).…”
Section: Treatment Of Bipolar Disorder and Bioactive Compoundsmentioning
confidence: 99%
“… 254 found that it can improve the survival rate of cultured neural stem cells and progenitor cells, upregulate the activity of intracellular antioxidant enzymes and further protect nerve cells. On the other hand, gallic acid can effectively reduce the generation of ROS, significantly increase the activity of antioxidant enzymes in animal models of ketamine-induced mania and reduce the activity of AChE and oxidative stress in the hippocampus and striatum 255 . Teixeira et al.…”
Section: The Role Of Dietary Antioxidant Suplements In the Prevention...mentioning
confidence: 99%
“… 256 demonstrated the ability of gallic acid to prevent mitochondrial lipid peroxidation in a cellular model using thiobarbituric acid reactive substances (TBARS) as the biological endpoint. In addition, ferulic acid can rescue DA neurons in the SNc region and nerve endings in the striatum from rotenone damage, restore antioxidant enzyme (SOD and CAT) activity, prevent glutathione overconsumption, and inhibit lipid peroxidation 257 ( Table 3 ) 252 , 253 , 254 , 255 , 257 . However, further human clinical trials are needed to fully define the beneficial activities and therapeutic effects of phenolic acids on neurons.…”
Section: The Role Of Dietary Antioxidant Suplements In the Prevention...mentioning
confidence: 99%
“…It was observed that gallic acid decreased the hyperlocomotion of the animals, induced antioxidant properties, and prevented cholinergic disfunctions in the brain [ 33 ]. Moreover, quercetin, a flavonoid, also showed antioxidant properties and inhibition of protein kinase C [ 34 ]. Table 2 shows the most relevant plant-derived bioactive compounds with neuroprotective effects in BD patients.…”
Section: Bioactive Compounds From Plants As Antioxidant Anti-inflamma...mentioning
confidence: 99%